2020
DOI: 10.18805/ijar.b-4279
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Studies on the Skull Bones of Indian Mithun (Bos frontalis)

Abstract: Background: There is scanty information on the skull morphology of Indian mithun. Therefore, the present study has been designed to provide information on the morphology of the skull of Indian mithun. Method: The study was conducted on the skull bones of twelve (n=12) adult Indian mithun of either sex (n=6, male and n=6, female). The head region samples of naturally died mithun were collected from different parts of the Mizoram and Nagaland states of India from April, 2019 to March, 2020. Result: The skull of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In the development of the nervous system, PL of neural membrane is rich in long-chain polyunsaturated fatty acids (PUFA), such as docosahexaenoic acid (DHA) and the brain-FABP (BFABP; FABP7) is mainly detected in the prenatal brain with a relatively low level in the adult brain. Hepatic carnitine palmitoyltransferase 1 (CPT1A) is the primary isoform (Choudhary et al, 2022) which is found in the liver, spleen, kidneys, lungs, intestines, pancreas, brain and ovaries. Brain carnitine palmitoy ltransferase 1 (CPT1C) is mainly expressed in the brain.…”
Section: E25mentioning
confidence: 99%
“…In the development of the nervous system, PL of neural membrane is rich in long-chain polyunsaturated fatty acids (PUFA), such as docosahexaenoic acid (DHA) and the brain-FABP (BFABP; FABP7) is mainly detected in the prenatal brain with a relatively low level in the adult brain. Hepatic carnitine palmitoyltransferase 1 (CPT1A) is the primary isoform (Choudhary et al, 2022) which is found in the liver, spleen, kidneys, lungs, intestines, pancreas, brain and ovaries. Brain carnitine palmitoy ltransferase 1 (CPT1C) is mainly expressed in the brain.…”
Section: E25mentioning
confidence: 99%